A Systematic review on randomized clinical trials for direct oral anticoagulant in subjects with acute coronary syndrome: primary and secondary outcomes. - AlMazrouei, Nadia; Elnour, Asim Ahmed; Al Khidir, Israa Y.; Alharbi, Fai Mutaz; Alshammari, Hajer Shaty; Altwalah, Shroog Farhan; Alshammari, Aliyah Hamdan; Alshammari, Talal Ahmed; Alhajaji, Ibrahim Khalid; Alshammari, Majd Habib; Aljohani, Norah; Khaled, Yasmin; et al. (Pharmacy Practice (1886-3655))
Background: In recent years, direct oral anticoagulant (DOAC) has been projected for secondary prevention of recurrent ischemic events post-acute coronary syndrome (ACS). However, there is still uncertainty about the efficacy/safety of DOACs in sub-populations. We hypothesized that for those with ACS, the use of DOAC in addition to antiplatelet therapy proves non-inferiority/superiority/or safety in terms of reduction in ischemic events or bleeding. This review aimed to evaluate the efficacy and safety of DOAC in addition to single antiplatelet therapy (SAPT) or dual antiplatelet therapy (DAPT) as antithrombotic therapy in subjects with ACS. Methods: We have followed the methods of the PRISMA guideline to report the systematic review findings of included randomized controlled trials (RCTs), including adult patients with ACS. The intention to treat analysis was evaluated in all included trials, and the adverse events were reported. Findings: A total of 13 trials (105322 subjects) were included in this systematic review. In subjects (both genders) with STEMI, the combination of rivaroxaban and aspirin (DATT) was associated with lower mortality in comparison with aspirin alone with or without PCI. Adding low-dose rivaroxaban to aspirin improved the primary efficacy outcome in subjects with a previous MI and those without. In subjects with STEMI or NSTEMI with or without PCI, the effects of DATT (rivaroxaban plus aspirin) were inferior to SAPT (aspirin therapy) for the primary safety endpoint and superior for primary efficacy outcome (MACE, CV death, MI, stroke). The twice-daily 2.5 mg dose of rivaroxaban reduced cardiovascular death rates but increased major bleeding rates. In subjects with AF who had successful PCI, a full-dose anticoagulation therapy with edoxaban 60 mg OD plus a P2Y12 inhibitor is non-inferior to triple antithrombotic therapy (TATT) with VKA about the risks of major or non-major bleeding events. Implications: Compared with TATT, DATT is associated with lower bleeding risks and mortality in subjects with ACS. While for subjects with ACS (STEMI/NSTEMI) with/without PCI, DATT (rivaroxaban plus aspirin) was superior to SAPT for primary efficacy outcome (MACE, CV death, MI, stroke). Nevertheless, based on current guidelines for subjects with ACS and co-existing AF, DOAC should be preferred over VKA supported by a favorable risk/benefit profile. The newer and more potent P2Y12 inhibitors (ticagrelor and prasugrel) are recommended over the former clopidogrel. Further, research needs to address the evidence-based indications of the DOAC members in subjects with specific comorbidities (e.g., AF, HF) and the transitioning between antithrombotic regimens.